2022
DOI: 10.1080/21678421.2022.2150556
|View full text |Cite
|
Sign up to set email alerts
|

A survey of current practice in genetic testing in amyotrophic lateral sclerosis in the UK and Republic of Ireland: implications for future planning

Abstract: This survey has 10 questions in addition to demographic data. It should take less than 5 minutes to complete.This survey aims to determine current UK practice for genetic testing in patients diagnosed with apparently sporadic Motor Neuron Disease/Amyotrophic Lateral Sclerosis (MND/ALS). This is particularly relevant in the context of upcoming changes in the provision of genetic testing in the NHS and emerging therapies targeting monogenic MND.It does not address the acknowledged absence of consensus for the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A recent survey of English neurology consultants identified variability in offering GS for pwMND; less than 50% would discuss GS with newly diagnosed pwMND. 10 Our findings illustrate a low proportion of neurology clinicians discuss the possibility of predictive genetic testing. A recent global survey of neurologists found that only 48% discuss predictive testing.…”
Section: Discussionmentioning
confidence: 80%
“…A recent survey of English neurology consultants identified variability in offering GS for pwMND; less than 50% would discuss GS with newly diagnosed pwMND. 10 Our findings illustrate a low proportion of neurology clinicians discuss the possibility of predictive genetic testing. A recent global survey of neurologists found that only 48% discuss predictive testing.…”
Section: Discussionmentioning
confidence: 80%
“…The current public-facing and staff resources are a starting point, yet a standardized approach is needed to ensure equitable access to tailored information and training. The research landscape around MND genetic testing, predictive testing and personalized medicine is rapidly increasing ( 6 ). Staff require upskilling to support proactively the conversations around these complex genetics of MND, and their consequences for pwMND and their family members.…”
Section: Discussionmentioning
confidence: 99%
“…1 It is predicted that increasing numbers of people with MND will access genetic testing, a consequence of widening eligibility criteria and genetically targeted clinical trials (with one genetically targeted therapy suggesting clinical benefit). [2][3][4] This means more family members will become aware of their increased risk of developing the condition. The genetics of MND are complex, 5 but it is suggested that in up to 20% of people with MND, a pathogenic variant can be identified.…”
Section: Introductionmentioning
confidence: 99%
“…The typical survival from symptom onset is 2–5 years 1 . It is predicted that increasing numbers of people with MND will access genetic testing, a consequence of widening eligibility criteria and genetically targeted clinical trials (with one genetically targeted therapy suggesting clinical benefit) 2–4 . This means more family members will become aware of their increased risk of developing the condition.…”
Section: Introductionmentioning
confidence: 99%